Street fighter the legend of Chun-Li - Bartkowiak, Andrzej; Aeillo, Patrick; Bartkowiak, Andrzej; Hyde Park Entertainment; Capcom Company; Adlabs Films; Twentieth Century Fox Home Entertainment (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2008)
Chun Li grows up and becomes a talented concert pianist. At the end of one of her concerts, she receives a scroll written in Ancient Chinese text. On her way home, she sees a mysterious homeless man getting assaulted by street thugs. After the thugs leave, Chun Li tends to him and notices a spiderweb tattoo on his hand. Nash and Maya investigate the murders of several heads of criminal syndicate families in Bangkok. On the side, Chun Li is meeting with a wise old woman in town who studies the scroll and tells her to find a man named Gen in Bangkok, revealing to her an image of the same spiderweb she saw tattooed on the homeless man's hand. Chun Li avenges her father's death at the hands of Bison and his evil Shadaloo Empire. The stage is set, the challenge is clear, and a legend will be forged
Director of photography, Geoff Boyle ; editors, Derek Brechin, Niven Howie ; music, Stephen Endelman
Cast: Kristin Kreuk, Chris Klein, Neal McDonough, Robin Shou, Moon Bloodgood, Josie Ho, Taboo, Michael Clarke Duncan, Pei-pei Cheng, Edmund Chen
DVD format
In Chinese or English with optional Chinese, English or Malay subtitles
Keywords: Martial arts films; Kidnapping -- Drama